(untitled) (Eurasian Medical Research Periodical, 2022)
Fine needle aspiration cytology (FNAC) is consider as an easy and simple procedure and technique for disease diagnosis in different parts or body organs including breast. Any breast mass or cyst, either benign or malignant can be evaluated by clinical examination, ultrasound, mammography, and FNAC before operation done and biopsy taken. Fine needle aspiration can be done by using different gauge needle for sample collection from the mass or the lesion for microscopic cytological evaluation, and it provide rapid minimal invasive diagnosis for the lesions